2011
DOI: 10.1177/0363546511420552
|View full text |Cite
|
Sign up to set email alerts
|

Low Range of Ankle Dorsiflexion Predisposes for Patellar Tendinopathy in Junior Elite Basketball Players

Abstract: This study clearly shows that low ankle dorsiflexion range is a risk factor for developing PT in basketball players. In the studied material, an ankle dorsiflexion range of 36.5° was found to be the most appropriate cutoff point for prognostic screening. This might be useful information in identifying at-risk individuals in basketball teams and enabling preventive actions. A history of ankle sprains might contribute to reduced ankle dorsiflexion range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
3
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 52 publications
2
109
3
10
Order By: Relevance
“…La limitación en la FD de tobillo representa uno de las causas que aumentan el riesgo de lesión del miembro inferior 40 . Se ha relacionado esta limitación con patologías de rodilla y de cadera 41 .…”
Section: Discussionunclassified
“…La limitación en la FD de tobillo representa uno de las causas que aumentan el riesgo de lesión del miembro inferior 40 . Se ha relacionado esta limitación con patologías de rodilla y de cadera 41 .…”
Section: Discussionunclassified
“…J. Backman and P. Danielson [5] showed that characteristic for basketball players increased traumatic hazard of ankle joint results in restriction of its mobility and reduction of bending angle. Such change results in emersion of patella pathologies.…”
mentioning
confidence: 99%
“…Although information is limited, there is a potential link between a history of ankle sprain and risk of injury at the knee joint. [16][17][18] The potential sensorimotor adaptations associated with CAI may not necessarily be protective for other joints. Identifying an underlying relationship between CAI and compensatory sensorimotor control in the knee may help clinicians and researchers to develop more comprehensive interventions to enhance global coordination in those with CAI and prevent future injury.…”
mentioning
confidence: 99%